2022
DOI: 10.3389/fevo.2022.805376
|View full text |Cite
|
Sign up to set email alerts
|

Roads Disrupt Frugivory and Seed Removal in Tropical Animal-Dispersed Plants in French Guiana

Abstract: Ecological interactions are being affected at unprecedented rates by human activities in tropical forests. Yet, the continuity of ecological functions provided by animals, such as seed dispersal, is crucial for forest regeneration and species resilience to anthropogenic pressures. The construction of new roads in tropical forests is one of the main boosters of habitat destruction as it facilitates human access to previously isolated areas and increases defaunation and loss of ecological functions. It, therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 89 publications
(156 reference statements)
0
4
0
Order By: Relevance
“…However, this key ecosystem service they provide can be diminished by human activity: ( i ) by reduced consumption of natural resources due to human provisioning close to roads; and ( ii ) by reduced effective seed dispersal, when seeds fall onto paved roads (Sengupta, McConkey & Radhakrishna, 2015). In many cases, seed dispersal by small mammals can compensate to some extent, however some plant species are reliant solely on large frugivores (Coutant et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…However, this key ecosystem service they provide can be diminished by human activity: ( i ) by reduced consumption of natural resources due to human provisioning close to roads; and ( ii ) by reduced effective seed dispersal, when seeds fall onto paved roads (Sengupta, McConkey & Radhakrishna, 2015). In many cases, seed dispersal by small mammals can compensate to some extent, however some plant species are reliant solely on large frugivores (Coutant et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, fruit surveys on the ground had shown a more significant proportion of Virola fruit with single valve husks at disturbed vs control forests 57 . However, the difference in seed removal rates across sites suggested that secondary consumers played an important role as alternative seed dispersers (e.g., toucans), eventually compensating for the disappearance of the primary seed dispersers 57 . This study shows that the nocturnal frugivore kinkajou complements the effects of birds as seed dispersers of Virola seeds.…”
Section: Discussionmentioning
confidence: 99%
“…
Figure 1 Study trees in the forested areas (FA) surrounding the ecological corridors along the National 2 Road between Régina and Saint-Georges in French Guiana (see further description in Coutant et al . 2022 57 ). The map was edited on ArcMap software version 10.6.1 ( https://www.esri.com/ ).
…”
Section: Introductionmentioning
confidence: 99%
“…suggests such an impact. In addition, a recent study highlighted the impact of the road RN2 on vertebrate community near SGO [61]. However, studies dealing with dung beetle and mammal co-occurrences are scarce [62].…”
Section: Discussionmentioning
confidence: 99%